2010
DOI: 10.1590/s0004-282x2010000100023
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit and hyperactivity disorder in people with epilepsy: diagnosis and implications to the treatment

Abstract: The association between attention deficit and hyperactivity disorder (ADHD) and epilepsy can cause significant impact on the social life of affected individuals and their families. Clinical studies suggest that 30-40% of people with epilepsy also have ADHD. There are no studies which demonstrate that short or long-term treatment with methylphenidate increases the risk of seizures. Some studies attempt to relate drug interactions between methylphenidate and antiepileptic drugs, but adverse effects of methylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 70 publications
3
18
0
3
Order By: Relevance
“…This is a surprising finding because scientifically, epilepsy is thought to possibly increase the likelihood of having ADHD. Koneski et al [27] in a review article identifies possible common pathophysiological mechanisms between epilepsy and ADHD, which may help further understand the high prevalence of ADHD among epilepsy patients. The finding of epilepsy being protective against ADHD in this study could be explained by having epilepsy as the most common condition among study participants (71%) and yet a smaller proportion of the participants had ADHD (11.7%) compared to the bigger proportion of the participants (88.3%) who did not have ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…This is a surprising finding because scientifically, epilepsy is thought to possibly increase the likelihood of having ADHD. Koneski et al [27] in a review article identifies possible common pathophysiological mechanisms between epilepsy and ADHD, which may help further understand the high prevalence of ADHD among epilepsy patients. The finding of epilepsy being protective against ADHD in this study could be explained by having epilepsy as the most common condition among study participants (71%) and yet a smaller proportion of the participants had ADHD (11.7%) compared to the bigger proportion of the participants (88.3%) who did not have ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that the relationship between these developmental disorders and epilepsy, particularly between ADHD and epilepsy, is very close, which is supported by evidence including research with animal models [1,2,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 91%
“…Formerly, it was reported that 30-40% of children with epilepsy had ADHD, while 5-60% of children with ADHD had epileptiform discharges on their EEGs, and 10-20% of them were diagnosed as having epileptiform discharges [1,2]. It is, thus, suggested that epilepsy and ADHD may be two different independent expressions of a common neurobiological abnormality.…”
Section: Comorbidity Of Epilepsy and Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with epilepsy often suffer from inattention, memory impairment, and deficits in processing speed, which may be due to seizures, interictal epileptiform discharges, underlying brain disease, or antiepileptic drugs (AEDs). [1][2][3][4][5][6][7][8] Cognitive and attentional symptoms in these patients may be managed by reducing seizures, decreasing AED polypharmacy, or switching to AEDs with fewer cognitive side effects, but this often does not result in resolution of the aforementioned deficits. 9 Cognitive rehabilitation has been used in patients with epilepsy, but systematic evaluation of this approach in this population is inadequate.…”
mentioning
confidence: 99%